Konişmentonun ispat fonksiyonu - Aydoğdu, Fatma (My University, 2006)
Konişmento, denizde taşıma sözleşmesini ispat etmekle birlikte taşıyanın eşyayı teslim aldığını yada gemiye yüklediğini gösteren ve taşıyanın kendisinin ibrazı karşılığında eşyayı teslimle borçlandıran bir belgedir. Konişmento hukuki fonksiyonları nedeni ile deniz ticareti alanında son derece önemli, kıymetli evrak niteliğine haiz bir belgedir. Konişmentonun eşyayı temsil fonksiyonu yanında en önemli fonksiyonu ispat fonksiyonudur. Konişmento navlun sözleşmesinin mevcudiyetini, şartlarını ve yükün taşıyan tarafından konişmentoda yazılı olduğu şekilde taşınmak üzere teslim alındığını ispatlar. Yükün miktarı, markası, haricen belli olan hal ve niteliği, cinsi, değeri konişmentoya yazıldığında aksi ispatlanabilir bir karine oluşturur. Konişmentoya, yükletenin malların ölçü, sayı veya tartısı, marklarıyla haricen belli olan hal ve mahiyetleri ile ilgili beyanları hakkında itirazı kayıt konulması halinde konişmento doğruluğu hakkında karine teşkil etmez.

Bill of lading means a document which evidences a “contract of carriage by sea” and the taking-over or trading of the goods by the carrier and by which the carrier undertakes to deliver the goods against surrender of the document. Due to its legal nature, bill of lading is a document which has an important role in sea-trade and is considered as a negotiable instrument. Bill of lading represents the goods to be carried and serves as a document of proof. Bill of lading proves the existence of “contract of carriage by sea”, conditions thereof, and the carrier’s receipt of the good, to be carried out, as stipulated in the bill of lading. When the amount, trade mark, out-seen conditions, type and value of the good are stated in the bill of lading, it creates a prima face evidence thereon. If any objection, about the measurement, amount, weight, trade-mark and out-seen conditions of the good, is stated in the bill of lading, then, the bill of lading does not create estopel on the validity of the content thereon.
Keywords: Hukuk; Özel Hukuk